Tension loading of a functionally graded bar - Muhammad Fadhil Bin Jailani (Nanyang Technological University, 2023)
Functionally Graded Material is a new type of non-homogenous materials with its material properties tailored to fulfil a specific performance or function. To design a FGM with a specific mechanical property, it is necessary to analyse the distribution of stress and displacement when force is applied to the material. However, no study has been conducted on a functionally graded rod with a nonlinear gradient under pure axial force. This research is to investigate the effect of pure axial loads on a functionally graded rod with varied linear and non-linear gradients. To investigate how the mechanics of a material are affected by its gradient, various stresses and displacements of rods with different gradients subjected to uniaxial tension loading are investigated analytically and numerically using Wolfram Mathematica. The types of gradients investigated are linear, quadratic, and sinusoidal gradients. The optimal gradient is determined through the comparison of different types of gradients.